2020
DOI: 10.2147/jhc.s271091
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-3 Encoded by Hepatitis B Virus Downregulates PTEN Protein Expression and Promotes Cell Proliferation</p>

Abstract: Purpose Chronic hepatitis B virus (HBV) infection is a key determinant of hepatocellular carcinoma (HCC). However, the mechanism by which HBV contributes to the development of HCC remains to be further explored. HBV-encoded miR-3 (HBV-miR-3) is a newly discovered microRNA that can affect the replication of HBV, but its influence on host genes is unclear. The tumor suppressor phosphatase and tensin homolog (PTEN) is expressed at low levels in most cancer cells. How HBV-miR-3 acts on PTEN to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…HBV-miR-3 enhances IFN production, activates JAK/STAT signaling, affects macrophages polymerization/depolarization, and induces the production of interferons and IL-6 by repressing SOCS5/STAT1 pathway ( Figure 3 A) [ 31 ]. Moreover, HBV-miR-3 interacts directly with the Protein phosphatase 1A (PPM1A) and Phosphatase and TENsin homolog (PTEN), silences these human genes, and enhances cell invasion and proliferation in HCC development [ 30 , 32 ]. Furthermore, HBV attenuates its replication targeting its HBV 3,5 kb mRNA transcript with HBV-miR-3 to reduce the expression of HBV core proteins (HBc) and the level of pgRNA [ 28 ].…”
Section: Hepatitis B Genome Encodes For Two Viral Mirnas: Hbv-mir-mentioning
confidence: 99%
“…HBV-miR-3 enhances IFN production, activates JAK/STAT signaling, affects macrophages polymerization/depolarization, and induces the production of interferons and IL-6 by repressing SOCS5/STAT1 pathway ( Figure 3 A) [ 31 ]. Moreover, HBV-miR-3 interacts directly with the Protein phosphatase 1A (PPM1A) and Phosphatase and TENsin homolog (PTEN), silences these human genes, and enhances cell invasion and proliferation in HCC development [ 30 , 32 ]. Furthermore, HBV attenuates its replication targeting its HBV 3,5 kb mRNA transcript with HBV-miR-3 to reduce the expression of HBV core proteins (HBc) and the level of pgRNA [ 28 ].…”
Section: Hepatitis B Genome Encodes For Two Viral Mirnas: Hbv-mir-mentioning
confidence: 99%
“…HBV may promote HCC development through HBV‐encoded RNA, which can regulate HBV replication and induce hepatic fibrosis and carcinogenesis 127,128 . HBV‐encoded RNA may interact with host RNAs and genes to promote the proliferation of liver cancer cells 129–132 . Recently, some studies found that m6A modification of HBV RNA also played important roles in the regulation of hepatocarcinogenesis 133 .…”
Section: M6a In Hepatitis B Virusmentioning
confidence: 99%
“…They also found that HBV-miR-3 promoted polarization of M1 macrophages after downregulating SOCS5 and activating the STAT1 signaling pathway. Furthermore, HBV-miR-3 can downregulate PTEN and PPMIA protein expression, enhance HCC cell proliferation and invasion, and promote the development of HBV-related HCC [ 110 , 111 ]. A recent study found that HBV-miR-3 is only present in peripheral blood exosomes of chronic hepatitis B (CHB) patients, so it could be used for monitoring of HBV infection [ 112 ].…”
Section: Effect Of Exosomal Viral Components On the Tumor Microenviro...mentioning
confidence: 99%